Ulice Warszawy jako świadkowie powstania. Przemiany semantyki przestrzeni = Streets of Warsaw as witnesses of the uprising. Transformations of the semantics of space - Napiórkowski, Marcin (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The text is an attempt to describe historical transformations of the city from the perspective of the semantics of spae. Twentieth-century history of Warsaw is presented on the basis of changes in town planning and their reflection in literary texts. The basic subject of interest is the Warsaw Uprising, studied as a moment of total destruction of the city form created before the Second World War and as a constant reference point for post-war attempts to reorganise cit. The main instrument of description of space transformations is the opposition of life and death (familiar and alien, safe and dangerous).
Keywords: Warszawa; Powstanie Warszawskie - 1944; przestrzeń miejska; zmiana